Malay Graffiti In A Nineteenth-Century Lithographed Bombay Qurâan - Wieringa, Edwin (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2018)
A lithographed copy of the Qurâan, printed in Bombay (Mumbai, India) in 1881, was bought in Sumatra a few years later by a certain K. Bijls, a Malay-speaking Dutchman who made several markings in it which may be regarded as a form of âgraffitiâ, in the sense of markings asserting his ownership. This same person most probably also added a marginal calligraphic composition to the text, in a manner that is typical of Malay epistolography, perhaps prompted by an element on the printed page that was unfamiliar to him, hence catching his eye and imagination. Keywords: Qurâan, Bombay Islam, Marginalia, Arabic Script. Sebagai tanda untuk menegaskan kepemilikannya terhadap naskah tersebut. Orang yang sama ini mungkin saja juga menambahkan komposisi kaligrafi marjinal pada teks tersebut yang menunjukkan bahwa hal tersebut adalah tipikal epistolografi Melayu yang mungkin diminta oleh halaman yang tidak dikenalnya sehingga menarik pandangan dan imajinasinya. Dengan demikian tanda tanda khusus dan ruang kosong lainnya yang digunakan dalam naskah quran tersebut mungkin merupakan ciri khas dari pembacaan orang orang barat yang tidak pernah dikenal atau didengar oleh orang orang Indonesia. Kata Kunci: Al-Qurâan, Islam Bombay, Marginalia, Kitab Arab.